Between a Rock and a Hard Place: Teacher Professional Learning - Dianne Smardon; Jennifer Charteris (New Zealand Journal of Teachers' Work)
A market-driven model for in-service teacher development can potentially place the sustainability of professional learning initiatives at risk. As schooling improvement contracts become increasingly student outcome driven, we question whether this could compartmentalise processes of teacher learning. With an emphasis on fixed fiscal input and resulting student outcomes, in-service teacher educators (ISTE) and teachers are in the middle charged with making a significant difference. What are the practices that make this space in the middle a place where agentic learning takes place? Adopting a polemic stance, we invoke the ‘between a rock and a hard place’ metaphor to illustrate the way teachers and ISTE are currently politically positioned.